Nazwy pokojów zagadek jako element gier językowych między nadawcą a odbiorcą tekstu reklamowego - Drążek, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Escape rooms are a new form of a pastime. In Poland they have become growingly popular. Escape rooms originate from the USA and are dated back to the 1990s. The task of the game participants is to get out of the room in which they have been locked. In order to leave the room the participants must solve a series of previously prepared puzzles or riddles. The presence of onomastic games in language communication derives from the ludic, emotional, and semantic aspect, and the result is the acceptance of a name within a certain circle, paying attention to the object and its use for a specific purpose – attracting the largest possible number of customers, getting the recipients interested in the offer. Wittgenstein proposed a list of language game, which is still open. It seems that (semantic and structural) creation, functioning, and purposefulness of using many of the discussed chrematonyms may be viewed from the aspect of at least some of the games listed by him, just to mention the solving of riddles, speculating or joking. The interest in a name (and in consequence in an object) and the proper interpretation of the contents provided do not differ from guessing, presuming, reading the hidden information, expectations and meanings related to an object, to which the name has been assigned.
Keywords: escape rooms; language game; advertising test; playing with a language; name as a text